EXTH-12. PRECLINICAL AND CASE STUDY EXAMINATION OF THE COMBINATION OF THE CLPP AGONIST ONC201 WITH THE PI3K/AKT INHIBITOR PAXALISIB FOR THE TREATMENT OF DIFFUSE MIDLINE GLIOMA. (14th November 2022) - Jackson, Evangeline; Duchatel, Ryan; Persson, Mika; Mannan, Abdul; Yadavilli, Sridevi; Parackal, Sarah; Game, Shaye; Chong, Wai Chin; Jayasekara, Samantha; Le Grand, Marion; Kearney, Padraic; Douglas, Alicia; et al.
Abstract: Diffuse midline gliomas (DMGs), including those of the pons (diffuse intrinsic pontine glioma - DIPG), are pediatric CNS tumors recognized as the most lethal of all children's cancers. Palliative radiotherapy remains the only approved treatment, with survival just 9-11 months post-diagnosis. The brain-penetrant small molecule therapy, ONC201, shows preclinical and emerging efficacy in early-stage clinical trials. However, patients invariably develop resistance, with some patients and models completely refractory to treatment. Using a powerful combination of pharmacology, proteomics, genomics, epigenetics, in vitro and in vivo modeling, across ten international laboratories, we have uncovered mechanisms underpinning resistance to ONC201. We find ONC201 elicits antagonism of the Dopamine receptor D2 (DRD2), whilst also causing mitochondrial degradation through potent agonism of the mitochondrial protease CLPP. This drives proteolysis of the electron transport chain (ETC) proteins including Succinate dehydrogenase A (SDHA) and the critical mitochondrial tricarboxylic acid (TCA) cycle regulator, Isocitrate dehydrogenase 3B (IDH3B). Loss of TCA activity reduces α-ketoglutarate and inhibits lysine demethylation, increasing methylation of H3K4me3 and H3K27me3, thus, altering the epigenome of DIPG. Mitochondrial disruption elicited redox-activated RAS-PI3K/AKT signaling, counteracted using the PI3K/AKT inhibitor paxalisib. The combination of ONC201 and paxalisib synergistically extended survival of two aggressive DIPG PDX models (SU-DIPG-VI vehicle=73 vs. combination=100-days, p=0.0027; SF8626 vehicle=36 vs. combination=43-days, p=0.0002). Compassionate access to this combination (n=2 patients; immediately post-RT and following re-RT) resulted in dramatic reductions in tumor volume, extending overall survival for the patient at diagnosis and the patient at progression (e.g., MR axial diagnosis scan = 1554 mm 2, following twelve months on the combination, current tumor volume = 464 mm 2 (~70% reduction), patient remains in progression free survival, 15 months since diagnosis). The clinical utility of our preclinical data is currently under investigation in the PNOC022 clinical trial (NCT05009992).